Association of capsular polysaccharide locus 2 with prognosis of Acinetobacter baumannii bacteraemia. Issue 1 (31st December 2022) - Yang, Jia-Ling; Yang, Chia-Jui; Chuang, Yu-Chung; Sheng, Wang-Huei; Chen, Yee-Chun; Chang, Shan-Chwen
ABSTRACT: Acinetobacter baumannii causes healthcare-associated infections worldwide. Capsular polysaccharide (CPS) is shown an important virulence factor of A. baumannii both in vitro and in vivo . Capsule locus 2 (KL2) for CPS is the most common KL type and is associated with carbapenem resistance. It is unclear whether KL2 is related to the clinical outcome of invasive A. baumannii infection. Here we had followed patients with A. baumannii bacteraemia prospectively between 2009 and 2014. One-third of the unduplicated blood isolates were randomly selected each year for microbiological and clinical studies. The KL2 gene cluster was identified using polymerase chain reaction. A total of 148 patients were enrolled randomly. Eighteen isolates (12.2%) carried KL2, and 130 isolates (87.8%) didn't. Compared with non-KL2 isolates, KL2 isolates had significantly higher resistance to imipenem, sulbactam, and tigecycline. Compared with the non-KL group, in the KL2 group, the hospital stay before development of bacteraemia was longer ( P  < 0.001), a higher percentage had pneumonia ( P  = 0.004), and the white blood cell count was lower ( P  = 0.03). Infection with KL2 A. baumannii predicted mortality (adjusted hazard ratio [aHR], 2.03; 95% confidence interval [CI], 1.09–3.78; P  = 0.03), independently of the Pitt bacteraemia score (aHR, 1.34; 95% CI, 1.23–1.46; P  < 0.001) and leucopenia (aHR, 2.16; 95% CI, 1.30–3.57; P  = 0.003). Thrombocytopenia contributed to the effect of KL2 on mortality in bacteraemia (Sobel test P  = 0.01). Large-scale studies are warranted to confirm these findings and the underlying mechanisms deserve further investigation.